Neural networks utilization in the video game industry - V. V. Godin; A. E. Terekhova; D. N. Bulatov; I. А. Zaremba (Вестник университета)
The scope of the video game industry and the use of neural networks in it have been studied. The impact of this technology on the computer games development process has been analyzed, the efficiency of its application in this area noted. The generalized scheme of video games development with identification of the stages most favorable for neural networks application has been considered. The possibilities of artificial intelligence in the video game characters’ visual image development, starting from the idea stage, touching the concept creation and ending with the realization stage, have been studied. The possibility of optimizing this process by implementing neural network technology has been shown. The neural networks application in the processes of writing game scripts and implementing dialog voicing in a game has been analyzed. The difference between the variability of plots and conversations of game characters created with the use of artificial intelligence model has been shown. The future concept of using neural networks as a digital twin of a video game developer has been considered. Estimates of the video game industry development through the generative artificial intelligence implementation have been formulated. As the study result, the positive influence of neural networks application on the computer games development up to the possible full automation of the industry under consideration due to the active use of this technology in the near future has been proved.